Computerised curve deconvolution of TL/OSL curves using a popular spreadsheet program - Afouxenidis, D.; Polymeris, G. S.; Tsirliganis, N. C.; Kitis, G. (Radiation protection dosimetry, 2012)
This paper exploits the possibility of using commercial software for thermoluminescence and optically stimulated luminescence curve deconvolution analysis. The widely used software package Microsoft Excel, with the Solver utility has been used to perform deconvolution analysis to both experimental and reference glow curves resulted from the GLOw Curve ANalysis INtercomparison project. The simple interface of this programme combined with the powerful Solver utility, allows the analysis of complex stimulated luminescence curves into their components and the evaluation of the associated luminescence parameters.